SITUATION OF PATIENT MANAGEMENT WITH HYPERTENSION IN BAC TU LIEM DISTRICT, HANOI (Vietnam Journal of Community Medicine, 2022)
Hypertension is a chronic non-communicable disease that should be managed in the community andcan be incorporated into the management process.Objective: To evaluate the management of hypertensive patients in some wards in Bac Tu LiemDistrict, Hanoi city in 2017.Subjects: 185 hypertensive patients. Methods: Cross section, description.Results: Locally managed hypertensive patients were mainly over 60 years old, accounting for84.7%, the group under 40 had no patients. Among managed patients, health insurance paid upto 92.2%. Among 185 hypertensive patients, the number of patients who want to be managed anddispensed drugs at the hospital is 59.9%, 29.3% at the medical station, 7% at the health center, and3.8% at home. Locally managed hypertensive patients have basic knowledge about risk factors andtheir consequences, how to recognize and treat the disease. Patients with hypertension continue tohave needs for management and treatment at health stations and are provided with information aboutthe disease in the following forms: via television, ward radio, handouts and medical staff.Conclusion: The management of hypertension at health level should be paid more attention andattention.
Keywords: Hypertension, management, Bac Tu Liem.